Republic of Lithuania : Staff Report for the 2009 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that the Lithuanian economy is undergoing a severe adjustment, after years of rapid economic growth and financial integration. With the global financial crisis, the unwinding of the imbalances accumulated during the boom has led to a sharp economic contraction. Capital inflows came to a halt in late 2008 and reversed in 2009, and the current account deficit turned into a surplus. Executive Directors have recognized the authorities' strong commitment to maintain the currency board arrangement, which has served as a useful macroeconomic anchor.